Obstetric performance in elderly Nigerian women: A comparative study - Ezechi, OC; Kalu, BKE; Loto, OM; Ezeobi, PM; Nwokoro, CA (Nepal Journal of Obstetrics and Gynaecology, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Aims: To study the obstetric outcome in Nigerian women aged 35 years and above while comparing them with younger women matched for parity, socioeconomic class and body mass index. Method: A cohort of 132 pregnant women aged 35 years and above with another 269 pregnant women aged 20-25 years matched for parity, socioeconomic class and body mass index seen at the obstetric unit of a multidisciplinary proprietary hospital in Lagos Nigeria. Results: There were statistically significant difference between the two group in incidence of chronic hypertension (P = 0.02), gestational diabetes (P = 0.05), symptomatic fibroid (P = 0.01), frequent hospitalisation (P = 0.007), caesarean section (P = 0.005), operative vaginal delivery (P = 0.042), Induction of labour (P = 0.024) premature delivery (P = 0.001), low birth weight (P = 0.021) and congenital abnormality but not in Preeclampsia, malpresentation, obstetric haemorrhage, wound infection and multiple pregnancy . Conclusion: This study demonstrated that women at 35 years and above are high-risk group and should be closely supervised during pregnancy. Keywords: Elderly, Nigerians, obstetric performance doi:10.3126/njog.v2i1.1468 N. J. Obstet. Gynaecol Vol. 2, No. 1, p. 9 - 12 May -June 2007